Expression of the 6C3 antigen on murine hematopoietic neoplasms. Association with expression of abl, ras, fes, src, erbB, and Cas NS-1 oncogenes but not with myc (The Rockefeller University Press, 1987)
The monoclonal antibody 6C3 was used to test a wide variety of murine hematopoietic neoplasms for cell surface expression of a 160 kD glycoprotein (gp160(6C3)) previously shown to be expressed by neoplastic pre-B and some B lymphocytes transformed by Abelson murine leukemia virus (A-MuLV). This antigen was expressed on many pre-B and B cell lymphomas, but not on A-MuLV-transformed fibroblasts, T cell lymphomas, or myelomonocytic leukemias, gp160(6C3) was expressed by most early B-lineage spontaneous tumors, and early B tumors induced by replication-defective MuLV-containing oncogenes the products of which are associated with the cytoplasmic aspect of the plasma membrane, i.e., fes, abl, H-ras, bas, src, erbB, and Cas NS-1. By comparison, none of the early B lineage lymphomas induced by the "nuclear" oncogene avian v-myc MuLV, or arising in mice transgenic for a murine c-myc gene, or later B cell lineage stages bearing translocations of the c- myc locus expressed this antigen.